If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(8) + 4 = y Multiply -3 * 8 -24 + 4 = y Combine like terms: -24 + 4 = -20 -20 = y Solving -20 = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -20 + -1y = y + -1y Combine like terms: y + -1y = 0 -20 + -1y = 0 Add '20' to each side of the equation. -20 + 20 + -1y = 0 + 20 Combine like terms: -20 + 20 = 0 0 + -1y = 0 + 20 -1y = 0 + 20 Combine like terms: 0 + 20 = 20 -1y = 20 Divide each side by '-1'. y = -20 Simplifying y = -20
| 2x-3+103=180 | | .25(12x-8)=7 | | -24=7+4(f-8) | | 2+7x=x+38 | | 4(1+6x)=4-x | | (7x+6)+(5x+3)=(3x-9) | | 3(8)+4=y | | 7x+9=x-21 | | 3x^2-195x-46590=0 | | 5x-4=4+10x | | -24=7+4 | | b-4/9=12/5 | | 10-4x+x=9 | | y+7y=48 | | 12m+20=40 | | 5y+20=5(2-2y) | | a(a-7)+14=2a | | 3x-2+136=180 | | -9+6x=51 | | 0.7m=5.6 | | 10x+10-8x-15=2 | | 5x+10x=50 | | (x-8)(x+7)=-2r | | 5a^2+4a-3=0 | | 2a^3+5a^2-25a=0 | | (3m+13)=31 | | -8p=14 | | 2c-4c=4 | | (3m+13)= | | -6x-9+8x=4 | | 16+4x=(-32) | | x(12-x)=35 |